2016
DOI: 10.1371/journal.pntd.0004956
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Identification of Burkholderia pseudomallei and Near-Neighbor Species in the Malabar Coastal Region of India

Abstract: Accurate identification of pathogens with biowarfare importance requires detection tools that specifically differentiate them from near-neighbor species. Burkholderia pseudomallei, the causative agent of a fatal disease melioidosis, is one such biothreat agent whose differentiation from its near-neighbor species is always a challenge. This is because of its phenotypic similarity with other Burkholderia species which have a wide spread geographical distribution with shared environmental niches. Melioidosis is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Similar to the case with other regions, there has been an increase in case detection following improvement in laboratory diagnostic capabilities coupled with local awareness campaigns for medical practitioners (129). At present, there is limited environmental data regarding the geographical distribution and prevalence of B. pseudomallei infection in India (133,134). MLST data suggest that Indian isolates are distinct from international isolates, specifically Australasian and Southeast Asian strains.…”
Section: South Asiamentioning
confidence: 85%
“…Similar to the case with other regions, there has been an increase in case detection following improvement in laboratory diagnostic capabilities coupled with local awareness campaigns for medical practitioners (129). At present, there is limited environmental data regarding the geographical distribution and prevalence of B. pseudomallei infection in India (133,134). MLST data suggest that Indian isolates are distinct from international isolates, specifically Australasian and Southeast Asian strains.…”
Section: South Asiamentioning
confidence: 85%
“…Melioidosis is recognized as an emerging global problem and is an endemic disease of public health and clinical importance in tropical and subtropical regions of the world. Melioidosis results from an infection by the Gram negative saprophytic bacterium Burkholderia pseudomallei [1,2]. Infection occurs through skin and by inhalation when susceptible individuals are exposed to contaminated water and soil [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted along the Malabar coastal region of Kerala found that 22.7% of the Burkholderia spp. strains isolated were B. pseudomallei [ 28 ]. Both studies were conducted at a single time point and used culture followed by 16S rDNA sequencing rather than specific B. pseudomallei PCR.…”
Section: Review Of Melioidosis Cases and Presence Of B mentioning
confidence: 99%